“Uma família chamada Brasil”: família e política na ditadura do Estado Novo (1937-1945) - Wilke, Fábio Roberto (2017)
This work, affiliated to the Master's research line "Culture, Migrations and Work", of the Graduate Program in History of the Federal University of Santa Maria, sought to understand the political strategies used by the New State Dictatorship (1937-1945) , in relation to the family. For this, a theoretical archetype denominated "politico-social conception" was elaborated. This theoretical construction had as purpose to understand the actions used by the New State policy in relation to the family, within three fundamental milestones. First, from an authoritarian context, which manifested itself through the institutional structuring of the state and its repressive actions. Secondly, a ostensive discourse of national reconstruction, which exhibited as a central presupposition the national union through the principles of work, order and nationalism, a joint condition that also propitiated the normalization of circumscribed habits in the family environment. Finally, the political relationship between the State and the family. This relation referred to the eminently political implications that a polysemous concept such as the one of family could provide to a certain authoritarian mode of government. From the construction of the symbology of Getúlio Vargas as the "father of the nation", even to what was referred to the rhetoric of national unity through the idea of "Brazilian family." In order to make this relationship intelligible, the legal and political mechanisms of the State, as well as the speeches of Getúlio Vargas and Marcondes Filho, were among the documents investigated.